ANALISIS PERAN GURU DALAM MEMBENTUK KARAKTER SISWA KELAS XI DI SMA SWASTA HOYA SEJAHTERA KECAMATAN SOMAMBAWA - Ndruru, Wira'erni (FAGURU: Jurnal Ilmiah Mahasiswa Keguruan, 2025)
This research aims to determine the role of teachers in shaping student character and the obstacles in shaping the character of class XI students at Hoya Sejahtera Private High School, Somambawa District, South Nias Regency. Teachers are the main facilitators in schools, whose function is to explore, develop and optimize their potential so that they become part of a civilized society. The teacher's role in this research is as a demonstrator, class manager, mediator, facilitator, evaluator and motivator. This type of research is descriptive type qualitative research. Data collection used interview and observation methods. In analyzing the data, researchers used the Miles & Huberman model of qualitative data analysis and checked the validity of the research data using triangulation techniques. Based on the results of research and discussion, it shows that: the driving factors include: example from teachers, adequate facilities and infrastructure, providing motivation, namely awards in the form of added value to students who are active in learning activities. Inhibiting factors include: a) Factors within students, b) Environmental influences, c) Lack of attention from parents. 3) Efforts made to overcome the factors inhibiting character formation are a) Teachers providing understanding, b) Habituation of behavior, c) Reprimands, d) Awareness from parents and e) Effective communication.